Associations between dietary fatty acid patterns and non-alcoholic fatty liver disease in typical dietary population: A UK biobank study - Tian, Aowen; Sun, Zewen; Zhang, Miaoran; Li, Jiuling; Pan, Xingchen; Chen, Peng (Frontiers in Nutrition, 2023)
Background & Aims Dietary fatty acid composition is associated with non-alcoholic fatty liver disease (NAFLD). Few evidence had identified clear role of dietary fatty acid composition of typical diet in NAFLD. We aimed to investigate the relationship between dietary patterns and NAFLD in populations with typical diets and to explore the effect of fatty acid composition in dietary patterns on NAFLD. Methods Principal component analysis was used to identify 4 dietary patterns in UK Biobank participants. Logistic regression was used to estimate the association between dietary patterns and NAFLD. Mediation analysis was performed to evaluate the extent to which the relationship between dietary patterns and NAFLD was explained by dietary fatty acid combinations, as surrogated by serum fatty acids measured by nuclear magnetic resonance. Results A dietary fatty acid pattern (DFP1) characterized by "PUFA enriched vegetarian" was negatively associated with NAFLD risk. Serum fatty acids were significantly associated with DFP1 and NAFLD. Mediation analysis showed SFA (27.8%, p<0.001), PUFA (25.1%, p<0.001), ω-6 PUFA (14.3%, p<0.001), LA (15.6%, p<0.001) and DHA (10%, p<0.001) had significant indirect effect on the association between DFP1 and NAFLD. A dietary pattern characterized by "PUFA enriched carnivore" (DFP2) was not associated with NAFLD risk. Conclusions A PUFA enriched vegetarian dietary pattern with increased LA and DHA, may be beneficial for the treatment or prevention of NAFLD, while a "PUFA enriched carnivore" dietary pattern may n ot be harmful to NAFLD.